2022
DOI: 10.1016/j.diagmicrobio.2021.115566
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of observed and unobserved self-collection of saline gargle samples for the detection of SARS-CoV-2 in outpatients

Abstract: The diagnostic sensitivity of observed and unobserved self-collected saline gargle (SG) samples for the molecular detection of SARS-CoV-2 in adults and school-aged children was evaluated against a reference standard of health care worker (HCW) collected nasopharyngeal (NP) flocked swab. A total of 46 participants had a positive NP swab sample; of these, 10 were in the observed phase and 36 were in the unobserved phase. Only one matching saline gargle sample tested negative and this was in the unobse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…This typically included those who were close to the case during the school day, such as deskmates and close friends ( 11 ). Asymptomatic testing was done using serial, validated saline mouth rinse gargles at three time points: upon contact identification, 7 to 8 days after last exposure, and 10 to 14 days after last exposure ( 12 ). All other classroom contacts were asked to self-monitor for symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…This typically included those who were close to the case during the school day, such as deskmates and close friends ( 11 ). Asymptomatic testing was done using serial, validated saline mouth rinse gargles at three time points: upon contact identification, 7 to 8 days after last exposure, and 10 to 14 days after last exposure ( 12 ). All other classroom contacts were asked to self-monitor for symptoms.…”
Section: Methodsmentioning
confidence: 99%
“… 3 Nasal swab, saliva, or water mouth rinse/gargle have been the most studied alternative specimens for SARS‐CoV‐2 detection by RT‐PCR. 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 In the province of Québec, natural spring water gargle has been extensively used for SARS‐CoV‐2 detection following the G‐SPIT study that showed acceptable performance compared to oronasopharyngeal swab, particularly for symptomatic patients. 6 , 14 , 15…”
Section: Introductionmentioning
confidence: 99%
“…3 Nasal swab, saliva, or water mouth rinse/gargle have been the most studied alternative specimens for SARS-CoV-2 detection by RT-PCR. [4][5][6][7][8][9][10][11][12][13] In the province of Québec, natural spring water gargle has been extensively used for SARS-CoV-2 detection following the G-SPIT study that showed acceptable performance compared to oronasopharyngeal swab, particularly for symptomatic patients. 6,14,15 To improve turnaround time, point-of-care (POC) tests have been developed, allowing for rapid testing at or near the specimen collection site.…”
mentioning
confidence: 99%
“…After screening the titles and abstracts of the remaining articles, 45 full texts were screened (figure 1). On the basis of our selection criteria, 27 of those studies were excluded and 18 studies [28,29,35,36,[46][47][48][49][50][51][52][53][54][55][56][57][58][59] met our inclusion criteria (table 1). One study examined two study populations, of suspected infection and of confirmed cases, which were analysed separately [59].…”
Section: Resultsmentioning
confidence: 99%